Countering Cova: Frankfurt-Style Cases are Still Broken. - Levy, Neil (Ethical Theory & Moral Practice, 2014)
The article presents counterarguments on philosopher Florian Cova's view on "Frankfurt-style cases user manual," who presented two kinds of Frankfurt-style arguments against the principle of alternative possibilities and argued that the author's attack on the soundness of Frankfurt-style cases succeeded only against one kind. Also mentioned is the dialect of Cora's paper that highlighted that capacity/possibility distinction is sufficient to block arguments against Frankfurt-style cases.